Bentuk Penyajian Tari Sining Pada Masyarakat Gayo Aceh Tengah - Maghfirah Murni Bintang Permata; Rika Wirandi; Berliana Denada (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This paper aims to describe the form of presentation of the sining dance in the Gayo community of Central Aceh Regency. Sining dance is a dance whose form of movement is inspired by nature. The movements are pure and use a lot of mimitive movements. This dance is also one of the traditional dances that was extinct and was then made a revitalization effort by the Central Aceh Kuta Dance Studio. This study focuses the problem on the form of presentation of the Sining Dance. To analyze the problem, Soedarsono used the theory of presentation forms, which said that, the form of presentation in dance has an understanding of how to present a dance as a whole, including the main elements or elements that support dance. These elements consist of dance movements, floor design, make-up, costumes, performance venues, props, and accompaniment music. This research uses qualitative research methods. This study concludes that the movements contained in the sining dance are mimitive and spontaneous movements, and tend to describe balance. Using a gayo openwork costume, accompanied by traditional music and traditional Gayo musical instruments. With two adult male dancers. Using upuh ulen-ulen cloth. Using a props made of pile board measuring 1.6 meters high. The shape of the board which is used as the main property is adopted from the Bere Numah shape. Meanwhile, the sining dance performance venue is currently adjusting to the location of the show provided, both on stage and in the open field area.